Endovascular thrombectomy for acute ischemic stroke in the perioperative period of cardiac surgery - HUO Xiao⁃chuan; ZHANG Chen; ZHANG Wei⁃wei (Chinese Journal of Contemporary Neurology and Neurosurgery, 2024)
Ischemic stroke is a serious complication during the perioperative period of cardiac surgery. Endovascular mechanial thrombectomy is an effective treatment for acute ischemic stroke, especially for patients after cardiac surgery who cannot undergo intravenous thrombolysis. However, for this specific patients in the perioperative period of cardiac surgery, the proportion of mechanial thrombectomy is significantly lower than in non⁃cardiac surgery patients. The therapeutic effect of mechanial thrombectomy in this context is not yet fully clear and require extensive clinical research for further validation.